Identification of essential components of the S. cerevisiae kinetochore - Doheny, Kimberly Floy (Cell, 1993)
We have designed and utilized two in vivo assays of kinetochore integrity in S. cerevisiae. One assay detects relaxation of a transcription block formed at centromeres; the other detects an increase in the mitotic stability of a dicentric test chromosome. ctf13-30 and ctf14-42 were identified as putative kinetochore mutants by both assays. CTF14 is identical to NDC10CBF2, a recently identified essential gene that encodes a 110 kd kinetochore component. CTF13 is an essential gene that encodes a predicted 478 amino acid protein with no homology to known proteins. ctf13 mutants missegregate chromosomes at permissive temperature and transiently arrest at nonpermissive temperature as large-budded cells with a G2 DNA content and a short spindle. Antibodies recognizing epitope-tagged CTF13 protein decrease the electrophoretic mobility of a CEN DNA-protein complex formed in vitro. Together, the genetic and biochemical data indicate that CTF13 is an essential kinetochore protein.